Modelo de gestão e estratégias: o caso de duas cooperativas mistas de leite e café de Minas Gerais - Antonialli, Luiz Marcelo (2000)
The present research aimed at analyzing the influences of the management model on the strategies of two milk and coffee cooperatives in the southern region of Minas Gerais. Specifically speaking, an external analysis of the environment (threats and oportunities) in which cooperatives in general are exposed to was performed, as well as an internal analysis (positive and negative aspects) of such organizations; political articulations among the groups involved in the previous elections were investigated; the degree of influence of the change of the board, in formulation and implemention of the cooperatives strategies, was analysed, related to financial, economical and social indicators. Finally, the cooperators opinions about the validity of the principles which guide cooperativism, as well as their opinions about their own cooperatives management model were raised. As for the methodology, the research is descriptive conclusive, and also in the typology of case study. As for the collection of data, three techniques were adopted: individual interviews, documental analysis (the qualitative part of the research), and structured questionaire (the quantitative part) to which the discriminant analysis was applied aiming at verifying divergences in the cooperators opinions considering the rural producers size. The names of the cooperatives were omitted to protect both the organizations and the ones interviewed. The results showed that the main environmental threats to the cooperatives are: competition with dairy products (especially those produced by multinationals and the informal milk market); competition with agricultural input dealers; the cooperatives dependence on the Cooperativa Central de Laticínios do Estado de São Paulo (Central Paulista) to which they are affiliated, and the adaptation of the management model to the capitalist regime. The main oportunities detected were: the possibility of enlargement in the regions market of milk products to be explored through the producers own brand of products; convenient location of the cooperatives throughout the countrys southeastern region; the improvement of the Fernão Dias highway, which should enhance the regional market development, and finally, the vertical diversification in the coffee industrialization. The ones interviewed are aware that the cooperatives are exposed to enviromental influences. There is, however, a consensus that the responses from those organizations to the environment has been slow and bureaucratic, due mainly to the fact that the strategical decisions are made in a collegiate manner, in sporadic assembly meetings which, in general, have presented low participation of associates. The political articulations that occurred in the last elections, in both cooperatives, may as well be seen as having caused critical moments in those organizations, traumatically reflecting on everyone involved in the process (members of the winning and of the defeated groups, cooperators and employees). Following the elections at Cooperativa MINAS-1, it was verified that half of the members of the new Executive Board and Management Council had had directive job positions in the two previous administrations, which contributed to the continuity of the strategies formulated in the previous administrations whose influences were considered as positive, negative and nule. At Cooperativa MINAS 2, the oposition group took over. None of the members of the Executive Board and Council of Administration had had any administrative jobs at that cooperative during the two previous administration periods. Due to ideological divergences in the transition some strategies adopted by the previous administrators were not continued, which was considered as negative influence. As for the other strategies, the influences were considered as positive, negative and nule. In that sense, it was verified that there was a relationship between the directors stability in their administrative positions and the maintainance of the cooperatives strategies. The comparison of the strategies to financial, economical and social efficiency indexes has shown that Cooperativa MINAS-1 had a higher performance than that of Cooperativa MINAS-2 due to a smaller organizational structure and lower administrative costs. On the other hand, however, Cooperativa MINAS-2 proved to be more efficient as far as service rendering is concerned. The results of the discriminant analysis, considering the rural producers size, showed that the opinions given by the mini-producers and the small-size producers group diverged from those given by the medium and big producersgroup in the following reasearch variables: the principle of free adhesion should be eliminated; the cooperative should develop new criteria as for the cooperators payment based on volume and quality; the cooperation among cooperatives should be performed with basis on the partners efficiency and strategical interests, be it or not another cooperative or even a non-cooperative entity. Capital stock should be updated with basis on market interests instead of the usual maximum of 12% a year; it is not advantageous, or even good for the cooperative, when groups take over the power and stay in charge for a long period of time and, finally, cooperator who fail to play his part should be excluded from the cooperative. However, considering the management models in the cooperatives, it was verified that the most influencial factors in the cooperatives investigated were: the directors amateur managerial level, the absence of strategical planning, and, mainly, the political divergences among the interest groups involved in the dispute for power.